Studies on supported Zeigler catalysts - Keir, Douglas A. (1974)
The work reported in this thesis is a series of investigations designed to elucidate the nature of the olefin polymerisation reaction catalysed by a Ziegler-type system supported on magnesia and on rutile. All activation and polymerisation reactions were studied by direct vapour/solid or gas/solid interactions. Infrared spectroscopy was employed to present a qualitative picture of all stages of catalyst activation and to identify polymeric species formed when the catalyst was exposed to ethylene and propylene monomers. A quantitative investigation of catalyst activation on the magnesia support was undertaken using gravimetric and analytical techniques. In the light of these results a reaction scheme has been proposed for the production of active sites on the magnesia surface. In essentially similar scheme is proposed for activation of the rutile support. Polymerisation of ethylene and propylene monomers by the magnesia based catalyst was followed gravimetrically. A study of the process variables such as temperature, monomer pressure and the effects of feedstock impurities was undertaken in order to formulate a kinetic model for the system. Strong kinetic evidence is presented for mass transfer control of the polymerisation rate. Such a model was supported by studies of the nature of the polymer formed, which appeared as a coherent encapsulating film on the catalyst surface. In a further series of experiments the permeation properties of ethylene and propylene monomers in their corresponding polymers were investigated. It is proposed that the permeation parameters derived from these studies find parallels in the olefin polymerisation reaction and this is interpreted as further evidence for diffusion control of the polymerisation reaction.